Pearl millet incorporated sweet potato choco-filled cookies - C. Pradeepika; K. Athira; T. Krishnakumar; M.S. Sajeev; K. Hanume Gowda (JOURNAL OF ROOT CROPS, 2025)
Abstract Sweet potato and pearl millet are good sources of dietary fiber and health protective antioxidants with potential protection against chronic oxidative stress commonly associated with pathogenesis of non-communicable chronic diseases (NCDs). Therefore, targeting sweet potato and pearl millet in ethnic or functional food design address chronic oxidative stress-linked NCD challenges such as early stages of type 2 diabetes and its associated complications has significant merit. Thus, the aim of this study was to standardize the formulation for the development of pearl millet incorporated sweet potato choco-filled cookies. Among the eight different formulations based on completely randomized design, treatment five (T5) showed significantly higher nutritional and sensory characteristics. The protein content ranged between 2.61 to 4.75 mg 100 g-1 dry weight (dw), starch 39.59 to 45.58 mg 100 g-1 dw, fiber 0.21 to 0.51 mg 100 g-1 dw, ash 3.52 to 6.48 mg 100 g-1 dw. In addition, micronutrient analysis revealed the presence of good amounts of micronutrients such as calcium (0.99 to 3.40 ppm), iron (1.05 to 1.67 ppm), magnesium (0.27 to 0.34 ppm), zinc (0.16 to 0.27 ppm), and copper (0.04 to 0.09 ppm). Results of this study indicated that the compsotion containing 40% of sweet potato, 40% of pearl millet, and 20% of wheat flour showed higher nutritional and sensory attributes compared to other formulations.